Evaluasi Formatif Program Rehabilitasi Sosial Bagi Korban Perdagangan Anak(Studi Kasus Program Rehabilitasi Sosial Rumah Faye Batam) - Aprilianzah, Ranggi Lukfi; Bantarti, Wisni (UI Scholars Hub, 2020)
This research is about the evaluation of social rehabilitation program for children trafficking victims conducted by Rumah Faye Batam, which is generally aimed to restore the social functions of the victims. The thesis is formative-evaluative research using a qualitative approach specified to elaborate on the implementation of the program, and also to identify and analyze the supporting factors and the constraints as a foundation of the program development. The result of the research shows that in the implementation of social rehabilitation programs at Rumah Faye, there are 7 stages which include various activities that refer to the flow of services and also the logical framework that has been developed by Rumah Faye itself. Rumah Faye Batam is currently facing many issues internally and externally, such as the unavailability of professionals and other issues constraining the implementation of the program. On the other hand, the opportunity that the program has is not neglectable such as having resources to operate the program, cooperation with other similar parties, the involvement of volunteers, etc.